Anatomical and histological study of the arteries that irrigate the pancreas and small intestine of the alpaca (Vicugna pacos) - Barreto R., Rose (2019)
This study describes the arteries that irrigate the pancreas and small intestine of the alpaca by dissection, angiography, vascular repletion and histology. Six alpacas were used, of which four were older than two years and two were four months old. Macroscopically, the pancreas was mainly irrigated by the pancreatic duodenal cranial and caudal arteries; in addition, branches from the hepatic artery, splenic artery and the branch of the first jejunal artery. These arteries and branches entered the pancreas (left, right and body portions) forming anastomosis in the form of nets, inside the parenchyma. Histological techniques showed that alpaca arteries have two layers, compact and spongy, forming the adventitia tunic of the duodenal cranial and caudal pancreatic arteries, celiac and cranial mesenteric arteries. The caudal duodenal pancreatic artery had the thickest compact adventitial layer, this artery supplying the right pancreatic lobe, part of the left lobe and the duodenum.